On Inversion of Permitivity, Permeability and Conductivity (Journal of Partial Differential Equations, 2020)
In this paper, the invecsion or coefficients permitivity &#949, permeability &#956 and conductivity &#963 in Maxwell system is discussed. Under some smoothness conditions, we have proved the existence, uniqueness and extension theorems of the local solution to the inverse problem by means of an equivalent integral system. Stability, well-posed property of the solution and the property of the solution at the end point or the largest existence interval are also researched.
Keywords: Inverse problem; Maxwell system; largest existence interval; wellposed property